Numerical Analysis of Sand Reinforced With Small Diameter Model Steel Pile - Hazarika, H.; Mujah, Donovan; Watanabe, N.; Ahmad, F.; Yasufuku, N. (Asian Institute of Technology (AIT), Thailand, 2012)
The use of reinforcement steel bars and passive piles are the oldest method adopted in slope stabilization measure in which, their reinforcing mechanisms are designed to function independently. This research proposes new kind of piles, hereafter called small diameter steel piles (SDSP), which are able to resist both lateral and vertical forces in countermeasure against slope instability. In this paper, the reinforcing effect of different pile arrangement and failure mechanism in different ground densities of each arrangement were compared and examined through laboratory scale experiment (direct shear test) and 2D numerical analysis. The multi-row arrangement of the installed SDSP was observed to accommodate higher loads and larger deflection in overall slope performance as opposed to the conventional passive piles and reinforcing bars. Failure mode in dense ground is apparently governed by soil’s shearing resistance mobilized at a higher strain, while bending stiffness of the reinforcing material is more dominant in loose ground regardless of the piles arrangements.